قاعدة " ماحرم سدا للذريعة أبيح للمصلحة الراجحة" و تطبيقاتها الفقهية نماذج مختارة - زينب, لموشي (University of Eloued جامعة الوادي, 2019)
"يتناول هذا البحث قاعدة: ""ما حرم سدًّا للذريعة أبيح للمصلحة الراجحة"" وتطبيقاتها، وإشكاليتُهُ الرئيسية التي حاولت الإجابة عنها تتمحورُ حول نظرة الشريعة الإسلامية لهذه القاعدة وما مدى إمكانية الاستفادة منها في علاج النوازل المعاصرة. وقد جاء هذا الموضوع في ثلاثة مباحث: حيث ابتدأ أولُها ببيان مفهوم القاعدة، ثم بيان المعنى العام للقاعدة، وجعل ثانيها لعرض أدلة القاعدة، ثم العناية بضوابط المصلحة الراجحة، وعُنِيَ ثالثها بتطبيقات القاعدة وبيان أحكامها الشرعية. ومن النتائج الأساسية التي وَصلَ إليها هذا البحث، أنَّ هذه القاعدة تمثل جانباً من جوانب الموازنة بين المصالح والمفاسد، مما أدى هذا إلى تطبيقها في كثير من المسائل الفقهية المختلفة. وأوصي في هذا البحث بإفراد رسالة علمية تحتوي على المسائل والتطبيقات المعاصرة التي تندرج تحت هذه القاعدة نظراً لأهميتها " "This research deals with the rule: ""What is forbidden to the pretext of the pretext of the most important interest"" and its applications, and the main question that I have tried to answer is centered around the Islamic law view of this rule and the extent to which it can be used in the treatment of contemporary calamities. The first topic was to clarify the concept of the rule through the definition of its vocabulary, and then explaining the general meaning of the rule. And make the second to display the evidence of the rule, and then take care of the controls of the most important interest, and the third of the applications of the rule and the statement of the provisions of legitimacy. One of the main results reached by this research is that this rule represents an aspect of Balancing the pros and cons, which has led to its application in many different jurisprudential issues. I recommend in this research to write a scientific message containing the contemporary issues and applications that fall under this. "
مذكرة ماستر تخصص فقه مقارن
Keywords: سد الذريعة, التحريم , الاباحة , المصلحة الراجحة; What is forbidden to the pretext of the pretext of the most important interest